Laparoscopic hemicolectomy for a patient with situs inversus totalis: A case report. (2017) - Sasaki, Kazuhito; Nozawa, Hiroaki; Kawai, Kazushige; Hata, Keisuke; Kiyomatsu, Tomomichi; Tanaka, Toshiaki; Nishikawa, Takeshi; Otani, Kensuke; Kaneko, Manabu; Emoto, Shigenobu; Murono, Koji; Watanabe, Toshiaki
Highlights: We report an interesting case with ascending colon cancer and situs inversus totalis (SIT) who underwent laparoscopic hemicolectomy. SIT is a rare congenital anomaly with an incidence rate of 1 per 5000–10, 000 adults. In cases of SIT, the left and right aspects of the thoracic and intra-abdominal organs are inverted, like a mirror image. Abstract: Introduction: Situs inversus totalis (SIT) is a rare congenital anomaly in which the left and right aspects of the thoracic and intra-abdominal organs are inverted, like a mirror image. Surgical procedures in a patients with SIT is difficult as their anatomy is abnormal. In particular, laparoscopic procedures are considered more difficult in patients with SIT because of the mirror-image anatomy. Presentation of case: The patient was a 75-year-old woman with ascending colon cancer. Laparoscopic hemicolectomy with radical lymphadenectomy was performed. After surgery, no specific complications developed. On the ninth postoperative day, the patient was discharged from our hospital. Recognition of the inverted anatomy by the surgeon using preoperative imaging permitted safe operation using techniques not otherwise differing from those used in ordinary cases. Discussion and conclusions: Laparoscopic colectomy is considered to be a safe and feasible option for patients with colorectal cancer and SIT.